C Corey Franklin New member Joined Sep 20, 2006 Messages 3 Sep 20, 2006 #1 Here's the equation: 9(x + 3) = 4x - 3 I just need help with the process.

M me New member Joined Sep 20, 2006 Messages 4 Sep 20, 2006 #2 first apply the distributive property 9x+27=4x-3 then combine like terms 27=5x-3 then add 3 to each side 30=5x now divide each side by 5 to cancel out the 5 so only x is left 6=x

first apply the distributive property 9x+27=4x-3 then combine like terms 27=5x-3 then add 3 to each side 30=5x now divide each side by 5 to cancel out the 5 so only x is left 6=x